Development of Women's Entrepreneurship and the Role of Women in SMEs - Hayu Lusianawati; Nurdiani, Tanti Widia; Hayati, Feb Amni (Westscience Press, 2023)
This research delves into the intricate landscape of women's entrepreneurship within Small and Medium Enterprises (SMEs) in Indonesia, examining the challenges, opportunities, and the broader societal implications. Employing a mixed-methods approach, we surveyed 500 women entrepreneurs and conducted in-depth interviews and case studies to provide a comprehensive understanding. The quantitative analysis illuminates the demographic profile, business characteristics, and challenges faced, while qualitative insights offer depth and context. Thematic analysis captures the narratives of resilience, determination, and community impact. The findings contribute to the discourse on women's entrepreneurship, guiding policymakers, businesses, and support organizations toward fostering a more inclusive entrepreneurial environment in Indonesia.